Editorial: Celebrating 50 Years of Grounded Theory - Astrid Gynnild (Grounded Theory Review: An International Journal)
Welcome to this very special issue of the Grounded Theory Review. In this issue we celebrate 50 amazing years of grounded theory during which it has become one of the fastest growing methods in the global research world. Five decades after The Discovery of Grounded Theory was first published, the seminal work of founders Barney G. Glaser and Anselm Strauss is cited more than 94,000 times on Google Scholar alone.